Novel plate-stratiform nanostructured Bi12O17Cl2 with visible-light photocatalytic performance. Issue 1 (17th February 2016) - Zhao, Mei; Dong, Lifeng; Zhang, Qian; Dong, Hongzhou; Li, Chengdong; Tang, Hongyan
Abstract : Novel plate-stratiform nanostructured Bi12 O17 Cl2 was studied with its visible-light photocatalytic performance. The Bi12 O17 Cl2 photocatalyst synthesized by a solid-state reaction was constructed of dozens of primary nanosheets, which were stacked by a parallel array of ultrathin secondary nanosheets. The microstructure and crystal structure of Bi12 O17 Cl2 primary and secondary nanosheets were discovered by high-resolution transmission electron microscopy and selected-area electron diffraction analyses. Its absorption edge was determined as about 590 nm and the band gap energy was 2.1 eV. The Bi12 O17 Cl2 nanomaterial exhibited superior visible-light-responsive photocatalytic activity and confirmed successful photodegradation of methyl orange (MO) under visible-light irradiation. The degradation efficiency was up to 97% in 90 min. Furthermore, the Bi12 O17 Cl2 photocatalyst exhibited excellent photostability and high mineralization capacity for MO photodegradation reaction. The MO photodegradation process was dominated by the direct photocatalytic mechanism. The contribution from its morphology and microstructure to superior photocatalytic activity was discussed.